The Role of the United Nations Human Rights Council (UNHRC) on Human Rights Violations Investigation in Yemen 2018-2021 - Clarita, Atalya; Suwecawangsa, Adi Putra; Dewi, Putu Ratih Kumala (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 4 No 4 (2025): JURNAL DIKSHI, 2025)
This research aims to explain the role of UNHRC in human rights violations that occurred in Yemen as a result of the armed conflict. UNHRC plays its role as an actor who investigates indications of human rights violations. This research uses the concept of The United Nations and Its System and the concept of Human Rights Investigation to analyze the issue. This research found that the UNHRC plays the role of an actor in its domain as an international organization under the UN with a focus on human rights This role is realized through the investigation of human rights violations in Yemen during the period 2018-2021, under a working mechanism known as the UN-mandated investigation. In the case of Yemen, this mechanism was realized by presenting an expert group, namely the Group of Eminent International and Regional Experts (GEE). This research concludes that the UNHRC roles as an actor is aiming to carry out investigations of human rights violations as a form to support the accountability process for all perpetrators who are proven guilty and to fight for the fulfillment of human rights for victims of human rights violations and all Yemeni civil society.